2021
DOI: 10.1287/mnsc.2019.3550
|View full text |Cite
|
Sign up to set email alerts
|

The Last Mile Matters: Impact of Dockless Bike Sharing on Subway Housing Price Premium

Abstract: Dockless bike sharing provides a convenient and affordable means of transport for urban residents. It solves the “last-mile problem” in public transport by reducing the travel cost between home and subway stations and thus increasing the attractiveness of distant apartments. This may affect the relationship between housing price and distance to subway and reduce the price premium enjoyed by proximate apartments. Using resale apartment data in 10 major cities in China, a difference-in-differences approach at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…one mode compensates for the disadvantages of another. For example, studies have shown that bike-sharing has a complementary effect on public transit by helping to overcome the last-mile problem (Chu et al. , 2021; Tang et al.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…one mode compensates for the disadvantages of another. For example, studies have shown that bike-sharing has a complementary effect on public transit by helping to overcome the last-mile problem (Chu et al. , 2021; Tang et al.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…bike sharing) and transit accessibility can generate positive synergistic effects on property values. Chu et al ( 2021 ) estimate that the entry of dockless bike sharing reduces the subway premium in house prices by about one-third. The above two papers highlight the positive value of bike sharing as a complement to the subway system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For another, BS is seen as a convenient and effective way to solve the ‘last mile’ problem for office workers. [ 27 , 28 ]. However, considering the influence factors on travel behavior will vary with individual attributes, there is a lack of the travel behavior differences between college students and office workers groups.…”
Section: Introductionmentioning
confidence: 99%